Strange and stranger ruralities: Social constructions of rural crime in Australia. (June 2015) - Scott, John; Hogg, Russell
Abstract: Rural crime has largely been understood through social disorganization theory. The dominance of this perspective has meant that most research into rural crime has tried to resolve perceived strains in communities, rather than analyze how social problems are constituted in rural places. UsingElias and Scotson's (1994) account of established-outsider relations, the paper examines how the organizational capacity of specific social groups is significant in determining the quality of crime-talk and responses to crime in isolated and rural settings. In particular social 'oldness' and notions of what constitutes 'community' are significant in determining what activities and individuals or groups are marked as features of crime-talk in these settings. Highlights: There is a paucity of research on the social construction of crime in rural places. Socio-organisational aspects of rural places are criminogenic, informing reactions to crime. Power relations inform how rural crime is socially constructed. Social 'embeddedness' is a key power differential in rural places.